English instruction approaches among Indonesia secondary educators in a multilingual context - Zainuddin; Tomislav Babić (Early Publishing Group, 2025)
This study explores English instruction approaches among Indonesian secondary school teachers within multilingual classrooms, emphasizing the significance of effective pedagogical strategies in a linguistically diverse educational context. Given Indonesia's rich tapestry of local languages alongside Bahasa Indonesia and English, understanding how teachers adapt their methods to accommodate multilingual realities is crucial for enhancing language learning outcomes. The current research primarily focuses on teacher beliefs, language policies, and macro-level educational discourses, with limited empirical investigation into the specific instructional practices employed in response to students' linguistic diversity. This highlights the need for granular, classroom-based data on pedagogical decision-making in multilingual settings. The research aims to identify prevalent English teaching methods and analyze how multilingual environments influence pedagogical choices. Employing a mixed-methods research design, the study involved 120 teachers from 24 schools, selected for their regional and institutional diversity. Data collection included structured questionnaires assessing instructional approaches, semi-structured interviews exploring teachers’ perceptions and strategies, and classroom observations capturing real-time practices. Data analysis involved descriptive statistics to identify dominant approaches and thematic coding to interpret qualitative data. The findings indicate that teachers predominantly employ communicative and genre-based approaches while tailoring their methods to leverage students’ linguistic backgrounds. Teachers also adapt techniques to reduce language anxiety and incorporate digital tools for greater engagement. These findings suggest that contextualized, culturally sensitive pedagogies can enhance language acquisition in multilingual classrooms. The study’s implications underscore the importance of teacher training programs that address multilingual challenges and propose policy adjustments that support inclusive, context-responsive language instruction. Overall, this research contributes valuable insights for educators, policymakers, and researchers seeking to optimize English education in diverse linguistic environments.